PENGARUH PROFITABILITAS, SOLVABILITAS DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rudianti, Walid (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2022)
The company's financial statements going public must be reported annually to the Financial Services Authority no later than the end of the fourth month after the financial year ends, if the company is late in reporting the financial statements then there is an audit delay. Factors that cause audit delays are company size, profitability, solvency, company age, audit opinion, solvency and so on. The author establishes the companies of the property and real estate sectors, Because many investors are interested in investing in property and real estate companies, the need for financial statements is also increasing so that audit delays are expected to be smaller. This study aims to determine the influence of profitability, solvency and company size on audit delays.This research is quantitative descriptive with a research population of 65 companies. The sampling technique uses purposive sampling and data is sample of 16 companies. The analysis method used is Multiple Linear Regression.The results showed a partial relationship that profitability has a negative effect and solvency has a positive effect on audit delays, while the size of the company has no effect on audit delays. Based on the results of the study shows that the variables of profitability, solvency and company size affect audit delays. The conclusion of this study is that profitability has a negative effect because the higher the profitability, the lower the audit delay, solvency has a positive effect because the lower the value of the company's solvency, the smaller the audit delay and the size of the company has no effect because the small size of the company at the time of financial reporting has the same pressure so that it does not affect the occurrence of audit delays.